2014
DOI: 10.1093/ckj/sfu129
|View full text |Cite
|
Sign up to set email alerts
|

A novel LMX1B mutation in a family with end-stage renal disease of 'unknown cause'

Abstract: End-stage renal disease (ESRD) presenting in a familial autosomal dominant pattern points to an underlying monogenic cause. Nail-patella syndrome (NPS) is an autosomal dominant disorder that may lead to ESRD caused by mutations in the transcription factor LMX1B. Renal-limited forms of this disease, termed nail-patella-like renal disease (NPLRD), and LMX1B nephropathy have recently been described. We report a large family, from the North East of England, with seven affected members with varying phenotypes of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 30 publications
0
20
2
Order By: Relevance
“…). In previous reports, several patterns of pathology (such as MCD, FSGS and mesangial proliferative glomerulonephritis) were observed in patients manifesting renal‐limited phenotypes of LMX1B mutation . In this manner, light microscopy findings for this disease varied by disease duration.…”
Section: Discussioncontrasting
confidence: 59%
“…). In previous reports, several patterns of pathology (such as MCD, FSGS and mesangial proliferative glomerulonephritis) were observed in patients manifesting renal‐limited phenotypes of LMX1B mutation . In this manner, light microscopy findings for this disease varied by disease duration.…”
Section: Discussioncontrasting
confidence: 59%
“…We conducted an extensive literature search to identify studies describing the renal limited phenotype associated with LMX1B mutations6789. We identified four studies reporting three mutations in the LMX1B DNA binding homeodomains, these studies reported on six families with LMX1B mutations.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been observed that patients with NPS caused by a LMX1B mutation located in the homeodomain showed significantly more frequent and more severe renal involvement compared with patients with mutations outside of this domain3. More recently, a renal specific missense mutation (R246Q) in the homeobox domain of LMX1B (LMX1B R246Q ) has been reported by different groups in France, United Kingdom and Japan6789. In each of these families, all of the affected individuals presented with glomerular pathologies without skeletal or other extra-renal manifestations.…”
mentioning
confidence: 99%
“…NPS and glomerulopathy (AD) [69][70][71]144 Mutations associated with an isolated glomerulopathy are located in the homeodomain of LMX1B, possibly disrupting the interaction between LMX1B and (podocyte specific) DNA targets [69][70][71] …”
Section: Lmx1bmentioning
confidence: 99%
“…Finally, different inheritance patterns or mutation types in genes involved in syndromic kidney disease can cause an isolated kidney phenotype at the mild end of the phenotypic spectrum. Examples are mutations in LMX1B, which are associated with nail-patella syndrome (OMIM 161200) but can also cause an isolated glomerulopathy [69][70][71] , and mutations in OCRL1, which cause Lowe oculocerebrorenal syndrome (OMIM 309000), but also cause Dent disease 2 (OMIM 300555) 72 . Another example is provided by FRAS1 and FREM2, in which biallelic truncating mutations cause Fraser syndrome (OMIM 219000).…”
Section: Different Presentations Of the Same Phenotypementioning
confidence: 99%